Al-Musāhamah al-Thaqāfīyah li Jam’at Sharīf Hidāyatullāh al-Islāmīyah al-Ḥukūmīyah fī Taṭwīr Fikrat al-Ijtimā’īyah al-Dīnīyah - Nasuhi, Hamid; Darmanji, Agus (Studia Islamika, 2009)
This article attempts to analyze intellectual contribution by writing activity in mass media: newspaper and magazine. For reason, opinion writing in mass media is the most prominent and significant contribution. The objects of this research are UIN Jakarta researchers, lecturers, students, and alumni opinion writing. Finally, this article would like to affirm that UII{ Jakarta's alumni have a significant role in intellectual discourse, so UIN Jakarta has passed over its traditional role as Islamic educational institution. By the making public opinion in mass media, UIN Jakarta want to affirm its role as center of excellence.DOI: 10.15408/sdi.v16i2.483